What beliefs underpin teachers’ strategies for coping with student reticence in L2 classrooms? - Rich, Casey (2014)
Within English as a Second Language (ESL) and English as a Foreign Language (EFL) learning environments in East Asia there is a widely held concern for student reticence to participate in the classroom (Cheng, 2000; Wen and Clément, 2003; Ellwood and Nakane, 2009; Tani, 2006; Chanock, 2010; Zhou, 2013). While there has been some research into teachers’ beliefs about East Asian student reticence, this has largely been quantitative in nature (Flowerdew and Miller; 1995; Cortazzi and Jin, 1996; Ferris and Tagg, 1996; Tsui, 1996; Jones, 1999; Flowerdew, Miller and Li, 2000; Cheng, 2000; Jackson, 2002). This study looks at teachers’ beliefs about student reticence and second language (L2) willingness to communicate (WTC) by undertaking a qualitative analysis of two EFL teachers in China. Following on the work of Kang (2005), Cao (2011) and Peng (2012) the study posits a new Ecological Model as a framework for examining teaches’ beliefs and their responses to reticence within a highly dynamic and situation-specific context. It found that teachers’ believe class dynamic and student socio-cultural predispositions are the most significant factors of L2 WTC, and that teachers’ responses to reticence are largely directed at adjustments to class dynamic.